HGG-06. Phase 2 Study of Veliparib and Local Irradiation, Followed by Maintenance Veliparib and Temozolomide, in Patients with Newly Diagnosed High-Grade Glioma without H3 K27M or BRAF Mutations: A Report from the Children's Oncology Group ACNS1721 Study. (3rd June 2022) - Karajannis, Matthias; Onar-Thomas, Arzu; Baxter, Patricia; Butingan, Nina; Fuller, Christine; Gajjar, Amar; Haque, Sofia; Jabado, Nada; Lin, Tong; Lucas, John; MacDonald, Shannon; Matsushima, Celeste; et al.
Abstract: BACKGROUND: The outcome for pediatric patients with high-grade glioma (HGG) remains poor. Veliparib, a potent oral PARP1/2 inhibitor, enhances the activity of radiotherapy and DNA-damaging chemotherapy. Preclinical data indicates that veliparib crosses the blood-brain-barrier and enhances the efficacy of radiotherapy and temozolomide in IDH mutant and wild-type HGG models. ACNS1721 was a single-arm, non-randomized phase 2 clinical trial designed to determine whether treatment with veliparib and radiotherapy, followed by the poly (ADP-ribose) polymerase (PARP) inhibitor veliparib and temozolomide, improves progression-free survival (PFS) in pediatric patients with newly diagnosed HGG without H3 K27M or BRAF mutations compared to patient level data from historical cohorts with closely matching clinical and molecular features. METHODS: Following surgical resection, newly diagnosed children with non-metastatic HGG were screened by rapid central pathology review and molecular testing. Eligible patients without somatic H3 K27M or BRAF mutations were enrolled on Stratum 1 (IDH wild-type) or Stratum 2 (IDH mutant). Protocol radiochemotherapy consisted of involved field radiotherapy with concurrent veliparib at 65 mg/m 2 twice daily. Adjuvant chemotherapy consisted of up to 10 cycles of veliparib 25 mg/m 2 twice daily and temozolomide 135 mg/m 2 once daily for 5 days every 4 weeks. RESULTS: Both strata were closed to accrual for futility after planned interim analyses. Among the 23 eligible patients who enrolled on Stratum 1 and received protocol therapy, the 1-year progression-free survival (PFS) was 0.29 (SE = 0.09) and 1-year overall survival (OS) was 0.67 (SE = 0.10). Among the 14 eligible patients who enrolled on Stratum 2 and received protocol therapy, the 1-year PFS was 0.57 (SE = 0.15) and 1-year OS was 0.90 (SE = 0.09). CONCLUSION: Rapid central pathology review and molecular testing was feasible. The protocol therapy was well tolerated but failed to improve outcome compared to clinically and molecularly matched historical control cohorts.